Bangunan Sejarah Stasiun Jakarta Kota Sebagai Cagar Budaya - Musholiha, Nindya Retno Musholiha; Hidayatullah, Syarif; Roejanto, Juse (JURNAL TEKNIK SIPIL, 2024)
Jakarta Kota Station is better known as Beos Station, which is short for Bataviasche Ooster Spoorweg Maatschappij (East Batavia Railway Transportation Company). The Jakarta Kota area as an old area with relics of historical buildings from the Dutch East Indies era. The Jakarta city station is included. So that the development of the Jakarta Kota station must pay attention to the aspects of cultural heritage conservation as part of the effort to preserve the old Jakarta Kota area. This building also contains several significance which provide evidence that it is a historic building and has passed a long period of existence as a public building with its proper function until today. In this research, an analysis will be carried out regarding the significance form of Jakarta Kota Station as a Cultural Heritage building in Kota Tua, Jakarta. So that it is hoped that an appropriate effort will be obtained to preserve the Jakarta Kota Station building according to steps according to the preservation rules by competent and relevant parties in the preservation of Cultural Heritage buildings.